Badanie zaangażowania pracowników jako narzędzie diagnozy i doskonalenia jakości zarządzania zasobami ludzkimi - Balcerek, Anna (Employee Engagement Survey as a Tool of Human Resources Management Development, 2008)
Employee engagement survey is a method of increasing employees loyalty and their influence on a company. On temporary labour market in Poland keeping employees within one organization for longer seems to be a main problem of human resources managers. The paper shows the difference between employees satisfaction and their engagement. It also stresses how employee engagement influences on the company performance. Moreover, the article contains a review of tools used by various organizations to search human resources engagement. Information included in the paper might be helpful for practitioners who are interested in implementing the employee engagement survey in their organization, as well as for researchers who would like to begin their research in the subject. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 341-353